The impact of the pandemic on mothers and children, with a focus on syndemic effects on black families: the “Prenatal to Preschool” study protocol - Njoroge, Wanjikũ F. M.; Tieu, Tiffany; Eckardt, Devlin; Himes, Megan; Alexandre, Christina; Hall, Waynitra; Wisniewski, Kate; Popoola, Ayomide; Holloway, Kayla; Rodriguez, Yuheiry; Kornfield, Sara; Momplaisir, Florence; et al. (Frontiers in Psychiatry, 2024)
Introduction Racism, a known social determinant of health, affects the mental health and well-being of pregnant and postpartum women and their children. Convincing evidence highlights the urgent need to better identify the mechanisms and the ways in which young children’s development and mental health are adversely impacted by their mothers’ experiences of racism. With the additional stressor of the COVID-19 pandemic, the criticality of improving knowledge of these domains has never been starker. The proposed project will address these questions and move the field forward to create targeted, culturally informed preventative interventions, thus achieving mental health equity for all children and families. Methods This prospective research is a cohort study that will longitudinally observe the outcomes of a cohort of mothers and their children recruited during the initial phase of the COVID-19 pandemic. Data will be parent/caregiver questionnaires assessing mental health, racism, support, and resilience at multiple time points with the first beginning at 24 months, clinical interviews with mothers, electronic medical records of mothers, and videotaped dyadic interactions at child age 24 and 48 months. A subset of Black participants will be asked to participate in qualitative interviews at child age 36 months. Results Analyze will be performed within and across Black and Non-Latino/a/e/x white (NLW) groups, and comparing mothers and fathers/secondary caregivers. Descriptive and multivariate analyzes will be run to better characterize how young children’s development and mental health may be adversely impacted by their caregiver’s experiences of racism. Discussion This prospective longitudinal mixed-methods study evaluates the simultaneous effects of the COVID-19 pandemic and racism on mothers and their developing children to characterize cross-racial differences, providing insight into risk and resilience factors in early development and the peripartum period.